Audit Committee Characteristics in Driving ESG Performance under ESG Exposure Conditions - Alfita Rakhmayani; Rifki Adhi Prasetyo; Maya Aresteria; Dian Kusuma Wardani; Muhammad Agung Syaputera (KEUNIS, 2026)
This empirical study is based on Resource Dependence Theory (RDT) and investigates how the presence of the ESG Exposure variable affects the relationship between audit committee meeting attendance, audit committee independence, audit committee expertise and audit committee size with ESG performance. The results are obtained using Fixed Effect Model (FEM) with cluster-robust standard error on 461 firm-year observations of 91 companies listed on the Indonesia Stock Exchange (ISX) during 2016-2025, which is contrary to the traditional governance theory. There is little significant impact on ESG performance from the attendance of the meeting or independence, implying behaviours that are ceremonial in nature, and only expertise is a positive driver. The size of the committee has a strong negative impact as predicted by social loafing and coordination failure. The results of moderation analysis suggest that ESG Exposure, in general, does not strengthen the effectiveness of governance, but it significantly exacerbates the adverse impact of Committee Size in high-risk industries where the bloat of the committee negatively affects agile decision making on sustainability. The results indicate a need for a shift in regulation from quantitative structural indicators to norms of competency in cognition and engagement. Policymakers and shareholders of energy and emission-heavy industries should focus on governance based on "lean" and "competent," and not "social loafers" with too many members that perpetuate "social loafing pathologies" that lead to lower ESG performance and green stock prices.